Escalation of Capacity and Quality PS60 Casting Production by Gating System Modification - Primaningtyas, Widya Emilia; Purnomo, Dhika Aditya; Ariani, Silvi; Wulandari, Kiki Dwi; Alfanda, Benedicta Dian; Baiti, Risa Nurin (International Journal of Marine Engineering Innovation and Research, 2024)
A ship tank’s ventilation pipes protector, called PS60, is produced by an investment casting process using CF8M material. Shorter time production for PS60 products, occurred due to the rise of PS60 demand, resulting non class casting product quality. Reported that 15% of PS60 defective products were shown from each production group. Porosity defects are the most common defects found. Recalculating riser’s, runners’s, and ingates’s dimensions, then remodeling designs a mold gating system done in order to reduce the percentage of defective products and increase production capacity. Remodeling gating system and casting simulation done by ProCast 2018 software using New Advanced Porocity Module (NAPM). The casting simulation output was porosity defects location and percentage, which were further analyzed. The product produced using a mold Gating system with a new layout, had 314.73 cm3 of empty part in the mold cavity which was identified as a porosity defect which was 4.58% of the total volume of the cast product. The total value of  the porosity after remodeling decreases by 2.39% from the existing product. 93.3% of the cavity inside the product is categorized as macroscopic porosity defects that are centralized in the riser and pouring basin areas, where in the casting product finishing process, these areas will be removed. Modification of the Gating System in PS60 mold escalates twice of PS60 capacity production than the origin.